Indicators of Change: Exploring Trends in Racial, Socioeconomic, and Demographic Characteristics Across California Counties: California Association of Human Resources Organizations (CAHRO) & California State University Channel Islands Sociology Program - Sánchez, Luis; Carrillo, Janet; Eulogio, Paula; Farr, Jeremiah; Garcia, Brenda; Hernandez, Daniella; Jodzio, Cole; Magaña Garza, Tatiana; Magaña, Dalia; Martinez, Alexis; et al. (CBR@CSUCI: An annual volume of community-based research, 2019)
One of CAHRO’s stated goals is to “build the capacity of organizations addressing human relations issues through information sharing, training, and technical assistance”. This series of reports, a collaboration between CAHRO and CSU Channel Islands Sociology students, contributes to this goal by providing community stakeholders access to empirical results related to various forms of demographic, social, and economic changes taking place across select California counties from 2000 to 2016. Using data from the 2000 Census and 2012-2016 American Community Survey (ACS), we document trends taking place across four broad categories: racial and ethnic change, income inequality, housing inequality, and population aging. The goal is that CAHRO and its network affiliates can use these descriptive portraits to gain a better understanding of contemporary changes in their respective counties and identify particular areas of need. This series includes reports for the following counties: · Alameda · Orange · San Diego · Santa Clara · Kern · Riverside · San Francisco · Ventura · Los Angeles · San Bernardino · San Mateo